Characterising the influence of material condition and in-service property evolution of an AlSi-PES abradable on blade-casing interactions - Lye, Ryan (2024)
Environmental concerns are pushing manufacturers to improve the efficiency of their aero-engines. A reduction in compressor blade tip clearance can lead to an increase in the overall pressure ratio and thermal efficiency; however, this reduced clearance can lead to more frequent blade-casing interaction (rub) events. These clearance change types can be separated into two categories, the first of which being an axisymmetric clearance change which is uniform around the entire casing and can be caused by centrifugal loading of the blades or differences in rates of thermal expansion between components. The second type is asymmetric clearance changes which occur when eccentricity between the blades and casing exists in the form of either an off-centred rotor or casing ovalisation, often caused by hard landings, turbulence, or gyroscopic events during manoeuvres.